2015
DOI: 10.1111/1471-0307.12267
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensory quality of several commercial Brazilian chocolate milk beverages

Abstract: Five brands of Brazilian chocolate milk were subjected to physicochemical and acceptability analysis. The moisture content, fat content, pH and soluble solids content varied between 78.35 and 84.27 g/100 mL, 1.68 and 3.08 g/100 mL, 7.11 and 7.44, 14.0 and 19.0° Brix, respectively, while the ash contents and % lactic acid equivalents were similar. Four of the tested brands had acceptable scores in all attributes; however, one had lower acceptability scores and lower values for luminosity, chromaticity, b* and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
7
1
Order By: Relevance
“…They explained that greater amounts of whey results in a more astringency beverage, which is a negative factor. Della Lucia et al (2016) observed that viscosity contributes to product acceptance, but here there was no correlation between these two variables. Ma et al (2015) correlated soybean seed chemical traits, soymilk character and soymilk sensory attributes among 70 genotypes, and they found that soymilk sensory attributes are positively correlated with glycinin/beta-conglycinin protein ratio, soluble solid and oil content, but negatively correlated with glycitein and protein content.…”
Section: Sensory Analysiscontrasting
confidence: 56%
“…They explained that greater amounts of whey results in a more astringency beverage, which is a negative factor. Della Lucia et al (2016) observed that viscosity contributes to product acceptance, but here there was no correlation between these two variables. Ma et al (2015) correlated soybean seed chemical traits, soymilk character and soymilk sensory attributes among 70 genotypes, and they found that soymilk sensory attributes are positively correlated with glycinin/beta-conglycinin protein ratio, soluble solid and oil content, but negatively correlated with glycitein and protein content.…”
Section: Sensory Analysiscontrasting
confidence: 56%
“…Color is an essential parameter besides aroma, flavor, and mouthfeel for any product to appeal to consumers and hence influences their acceptance in the market (Della Lucia et al, 2016; Thompson et al, 2004). The sample’s lightness (L) value was slightly higher than the control as the sample contains half the amount of added sugar compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, whey proteins can be utilised as a substitute for milk in the production of beverages in which fruit pulps, chocolate and stabilisers can be added to enhance flavour and overall acceptability of the whey protein‐based dairy beverages (Della Lucia et al . ; Amaral et al . ; Cappato et al .…”
Section: Introductionmentioning
confidence: 99%